Fluid-structure interaction analysis and density-based topology optimization of single pad externally adjustable fluid film bearing operating in high-speed application - Harishkumar Kamat; Chandrakant R. Kini; B. Satish Shenoy (Ain Shams Engineering Journal)
Topology optimization has emerged as a promising technique to make the machines/machine components lightweight without compromising performance. This article investigates topology optimization of single pad externally adjustable fluid bearing operating in the high-speed application with two-way fluid–structure interaction (FSI) findings. The use of circular profile bearing in modern high-speed turbomachinery is limited due to hydrodynamic instability. Hence, advancements in the field of non-circular bearings, such as single-pad externally adjustable bearings, can be utilized to overcome this challenge. One-way FSI and two-way FSI analyses are performed initially on these as single-pad externally adjustable bearing working at various rotor speeds at a high eccentricity ratio. Further, using the results of two-way FSI, a density-based topology optimization (TO) technique is applied using ANSYS workbench software. TO results showed that the weight of the pad bearing can be reduced to 38.14%, which helps the bearing manufacturers to accurately predict optimum material distribution within the design space.